Variation of blood pressure during change of posture - Islam, Md Nazrul; Kamal, SK; Islam, Md Sirajul; Hossain, Sk Amir (Bangladesh Medical Journal Khulna, 2019)
Background: Many factors can influence blood pressure, one of which is body position. The aim of present study was to establish a specific pattern of blood pressure (BP) changes in accordance with posture changes in healthy adults. Objective: Aim of present study was to establish a specific pattern of blood pressure (BP) changes in accordance with posture changes in healthy adult male and females. Methods: Blood pressure was recorded by aneroid sphygmomanometer in supine, sitting and standing posture on both arms. Mean ± standard deviation of the observation for all the parameters were calculated and comparison in supine, sitting and standing position was done by repeated measures Analysis was done by ANOVA test and tukey's post hoc test. Results: Fifty healthy males and fifty healthy female took part in this study. BP varies according to body position. Both Systolic blood pressure and diastolic blood pressure was significantly decreased (P<0.05) while changing posture from supine to standing. But blood pressure changes during change of posture from supine to sitting or from sitting to standing was not significant (P>0.05). Conclusions: Change in body posture changes systolic blood pressure as well as diastolic blood pressure. Bang Med J (Khulna) 2018; 51 : 16-20